Pengetahuan Dan Persepsi Remaja Tentang Penyakit Menular Seksual - Siti Robiatun; Henri Soekirdi; Christina Pernatun Kismoyo (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Adolescent reproductive health problems are increasing from year to year, not to mention sexually transmitted diseases. Premarital sexual behavior occurs more frequently and very unfortunate many teen abortionsaction. Sexually Transmitted Diseases (STDs) has always been one endless problems to be discussed. Every year has increased the number of people with the disease PMS, there fore an increase in knowledge and perceptions of sexually transmitted diseases should be emphasized, especially in the adolescent group.Objective:To determine the relationship between knowledge and perceptions of adolescents about sexually transmitted diseases at Hasyim MTs students Piyungan Bantul, Yogyakarta.Methods:This research is analytic-correlation using cross sectional research design. Purposive samplingtechnique, with the enclosed questionnaire. Statistical data analysis using Pearson product moment test.Results:The level of knowledge categorized by 15 respondents (37.5%), a total of 19 respondents (47.5%) have sufficient knowledge as well as 6 respondents (15%) had less knowledge. Perceptions of STDs 13 respondents (32.5%) had a good perception about STDs, as many as 23 respondents (57.5%) had sufficient perception and by 4respondents(10%) perceiveless. Kendall-tau test results have p-value of 0612 with a significant level of 0.000.Conclusion: There is a relationship between knowledge and perceptions of adolescents about sexually transmitted diseases at Hasyim MTs Piyungan Bantul,Yogyakarta in 2011.Keywords: knowledge, sexually transmitteddiseases, perception